Rekabet Yasağı Sözleşmeleri - (:unkn) unknown (My University, 2016)
Bir işçinin, iş ilişkisi içerisinde işverenin müşterilerine nüfuz etmesi yahut iş sırlarını öğrenmesi nedeniyle iş sözleşmesi sona erdikten sonra, belirli bir faaliyet alanında, belirli bir coğrafi bölgede ve belirli bir zaman dilimi içerisinde işverenle rekabet teşkil eden davranış içerisine girmesini yasaklayan rekabet yasağı sözleşmesi, İş Hukukunun temel amacı olan sözleşmenin "zayıf" tarafı işçiyi işverene karşı korumanın bir nevî istisnasını teşkil etmektedir. Bu bağlamda işverenin haklı menfaatlerinin korunmasının amaçlandığı rekabet yasağı sözleşmelerinin hukukumuzdaki düzenlemesi çalışmanın ana konusunu oluşturmaktadır. Hem işverenin haklarını hem de işçinin çalışma ve sözleşme özgürlüğünü ihlâl etmeyecek biçimde yapılması gereken rekabet yasağı sözleşmeleri bu anlamda hukuken belli geçerlilik şartlarına tâbi tutulmuştur. Bu şartlara uyulmaksızın yapılan sözleşmelerin akıbetleri, yaptırımları ve aşırı yasakların sınırlandırılması da çalışmada yer almaktadır. Tüm şartları yerine getirilmiş hukuka uygun bir rekabet yasağı sözleşmesine aykırı davranan işçinin zararı tazmini, cezai şartı ödemesi ve aykırılığı durdurması gibi durumları da incelenmiştir. Son olarak, karşılaştırmalı hukukta işverenin haklı menfaatini koruyucu rekabet yasağı sözleşmesine benzer uygulamalar değerlendirilmiştir

The non-competition agreement prohibits employee to be involved in an act of competition after the termination of contract of employment, in a certain scope , in a certain geographic domain and in a certain period of time, this comes as a result of his access to customers of the employer or his knowledge regarding the business secrets within the employment relations, and being the primary aim of the labor law it constitutes a sort of exception in protecting the employee who is the "weak" side of the agreement, against the employer. In this context, the main purpose of this work is to explain the non-competition agreements in our legal system which aim to protect the legal interest of the employer. The non-competition agreements which should be organized to protect the rights of the employer and to avoid the violation of right to work and freedom of contract, is legally subjected to some conditions of validity within this regard. The work also includes the consequences and the sanctions of the contracts which are contravened these conditions and limitations of the extreme prohibitions. The work analyzes compensation of the employee who violated a noncompetition agreement that fulfilled all of the necessary conditions, discharging the penal clause and termination of the contrariety. Finally the work examines in comparative law the practices protecting the legal interest of the employer similar to the non-competition agreements
Keywords: Hukuk